The Meaning of Islamic Educational Institutions - Maspuroh; Tita Sumiati; Mohammad Nabiel Hadie Alfan; Nuri Handayani; Sahrul Ramadhan (Penerbit Hellow Pustaka, 2025)
Islamic educational institutions have an important role in shaping the character and morals of the younger generation. Islamic education, known as tarbiyah, focuses on the development of individual potential both intellectually and spiritually. This aims to create a society that is not only academically intelligent but also has high morals. Islamic education has a deep philosophical foundation, covering aspects of ontology, epistemology and axiology. In this context, education is not only seen as a process of transferring knowledge, but also as an effort to instill moral and ethical values ​​in accordance with Islamic teachings. The history of Islamic education began from the time of the Prophet Muhammad to the present, with significant developments in methods, materials, and places of education. In the modern period, Islamic education began to integrate general knowledge with religious teachings to prepare the younger generation to face global challenges. In facing the challenges of modernization and globalization, Islamic education must be able to adapt without losing its identity. The integration of religious values ​​and knowledge is the key to creating a strong and characterful generation.